Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Keaktifan Belajar Siswa di Sekolah Menengah Pertama Robbaniyyin Talang Bukit Kecamatan Bahar Utara Kabupaten Muaro Jambi - M. Arifky Fadilah; Ida Rianti; Siti Roudatul Jannah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The researcher used a qualitative descriptive research type at Robbaniyyin Middle School. The data sources were all 24 students in grade IX of Robbaniyyin Plus Middle School, Islamic Religious Education teachers and the Principal. Data collection instruments were observation, interviews and documentation studies. The results of this study indicate that there is student learning activity in the Islamic Religious Education learning process in grade IX of Robbaniyyin Middle School, namely students are active in writing, reading, speaking, listening, moving, discussing and asking and answering questions. Meanwhile, the factors that influence students in increasing their learning activity are from within the students, namely: healthy physique, having strong attention, perception and memory. From outside the students, namely: a place far from the sound of vehicles, facilities namely personal stationery, a clean room and a clean classroom whiteboard, then the teacher's varied learning methods such as the lecture method with the material of faith in Allah SWT, the practice method with the material of reading and writing the Quran and the method of presentation with the material of congregational prayer.